Poster 236: There is No Difference in Early Functional Outcomes for Patients Undergoing Tele-Rehabilitation versus Standard in Office Rehab after Arthroscopic Meniscectomy: A Randomized Controlled Trial. Issue 7 (30th July 2022) - Hurley, Eoghan; Vasavada, Kinjal; Lin, Charles; Gonzalez-Lomas, Guillem; Alaia, Michael; Strauss, Eric; Jazrawi, Laith; Campbell, Kirk; Mojica, Edward
Objectives: While a growing body of evidence has demonstrated that tele-rehabilitation is effective, the functional outcomes of patients undergoing tele-rehabilitation as compared to in-person rehabilitation after arthroscopic meniscectomy remains unclear. This is especially salient against the backdrop of COVID-19 and the Delta variant and the subsequent increased demand for remote care of these patients. Methods: A randomized-controlled trial was conducted including patients scheduled to undergo arthroscopic meniscectomy for meniscal injury by one of five fellowship trained sports medicine surgeons between August 2020 and May 2021. Patients were randomized to receive tele-rehabilitation, defined as exercises and stretches provided by trained physical therapists over a synchronous face-to-face video visit, or in-person rehabilitation for their post-operative course. International Knee Documentation Committee Subjective Knee Form (IKDC) score and Visual Analogue Scale (VAS) score were collected at timepoints of baseline, 3 months, 6 months, and 12 months post-operatively. Statistical analysis was conducted using Student T-test to assess for differences across the two groups. Results: An interim analysis was conducted on 60 patients with 6 month follow-up outcomes. There were no significant differences in VAS scores between groups at baseline (p =0.716) and 3 months postoperatively (p = 0.700). and 6 months postoperatively (p = 0.688). In addition, no significant differences in IKDC scores were seen between the groups at baseline (p = 0.146) and 3 months (p = 0.746). At 6 months, 24 patients were available with no significant differences observed across groups at this time point (IKDC; p = 0.633) (VAS; p = 0.688). Conclusions: Tele-rehabilitation is demonstrated to be as efficacious as traditional in-person rehabilitation following arthroscopic meniscectomy at up to 6 months post-op. This serves as a convenient and safe alternative for conventional patients during their post-operative course.